Technological and chemical properties of heat-treated Anatolian black pine wood - Akyıldız, Mehmet Hakan; Ateş, Saim; Özdemir, Hasan (African Journal of Biotechnology, 2009)
In this study the effect of heat treatment on air-dry density (Dm), oven-dry density (D0), shrinkage ( ), swelling (), fiber saturation point (FSP), compression strength parallel to grain (c//), bending strength (b), modulus of elasticity (MOE) in bending, Brinell-hardness (HB), equilibrium moisture content (EMC), chemical content and cellulose crystallinity of Anatolian black pine [Pinus nigra J.F. Arnold subsp. nigra var. caramenica (Loudon) Rehder] was evaluated. Specimens were subjected to heat under atmospheric pressure at 3 different temperature (130, 180 and 230°C) and 2 different time levels (2 and 8 h). The value of Dm, D0, , , FSP, EMC, c// , b, MOE, holocellulose, 1% NaOH and alcohol solubility decreased, whereas, lignin content increased depending on the heating temperature and the time. Cellulose crystallinity of the specimens was not changed significantly. 130°C showed minimum effect, on the other hand, 230°C showed maximum effect on all properties of treated wood. Accordingly, for heat treatment process, 130°C for 2 h should be applied in place where mechanical properties are important. However, 230°C for 2 h should be used in place where a physical property is preferred. Consequently, heat treated Anatolian black pine woods could be utilized in applications for several purposes such as kitchen furniture, outdoor furniture and windows frames.
Keywords: Anatolian black pine, heat treatment, physical, mechanical, chemical properties, FT-IR, crystallinity.